Sound-Meaning Correspondence and Child-Directed Speech in Early Language Development: Evidence From Kazakh Caregiver Speech - Zaure S. Sovetova; Anar Fazylzhan; Kuralay Kuderinova; Aiman Zhanabekova; Beisenkhan Samal; Yelimay Shynatay (Journal of Language Teaching and Research, 2026)
This study examines the phonological, semantic, and communicative features of caregiver speech and children’s self-created words in early language development, based on data from Kazakh-speaking families. The research is based on a survey of 50 parents and explores two key aspects: (1) the use of terms of endearment in child-directed speech, and (2) children’s spontaneous formation of novel words associated with object properties. The results show that nearly half of the respondents use non-standard, phonologically simplified expressions when addressing children, alongside traditional lexical forms. These expressions are characterized by reduplication, elongated intonation, and simple syllabic structures, and primarily convey emotional closeness, softness, and smallness. In addition, the findings reveal that children actively create their own lexical items (e.g., titi, buba, kiki), which systematically reflect sound–meaning associations. In particular, front vowels and high-frequency consonants tend to be associated with smallness and sharpness, whereas back vowels and labial consonants are linked to largeness and softness. These patterns are consistent with sound symbolism and the bouba–kiki effect, suggesting that such associations are present in natural language use and emerge early in development. Furthermore, the study demonstrates that children can use these invented forms consistently, indicating the formation of early lexical systems based on phonological and semantic regularities. The results support the view that early language is not entirely arbitrary but includes motivated, iconic relationships between sound and meaning. Overall, the findings highlight the role of caregiver input, phonological simplification, and cognitive biases in shaping early language acquisition.